Tnfaip2/exoc3‐driven lipid metabolism is essential for stem cell differentiation and organ homeostasis. (10th December 2020) - Deb, Sarmistha; Felix, Daniel A; Koch, Philipp; Deb, Maharshi Krishna; Szafranski, Karol; Buder, Katrin; Sannai, Mara; Groth, Marco; Kirkpatrick, Joanna; Pietsch, Stefan; Gollowitzer, André; Groß, Alexander; et al.
Abstract: Lipid metabolism influences stem cell maintenance and differentiation but genetic factors that control these processes remain to be delineated. Here, we identify Tnfaip2 as an inhibitor of reprogramming of mouse fibroblasts into induced pluripotent stem cells. Tnfaip2 knockout impairs differentiation of embryonic stem cells (ESCs), and knockdown of the planarian para‐ortholog, Smed‐exoc3, abrogates in vivo tissue homeostasis and regeneration—processes that are driven by somatic stem cells. When stimulated to differentiate, Tnfaip2 ‐deficient ESCs fail to induce synthesis of cellular triacylglycerol (TAG) and lipid droplets (LD) coinciding with reduced expression of vimentin ( Vim )—a known inducer of LD formation. Smed‐exoc3 depletion also causes a strong reduction of TAGs in planarians. The study shows that Tnfaip2 acts epistatically with and upstream of Vim in impairing cellular reprogramming. Supplementing palmitic acid (PA) and palmitoyl‐L‐carnitine (the mobilized form of PA) restores the differentiation capacity of Tnfaip2 ‐deficient ESCs and organ maintenance in Smed‐exoc3 ‐depleted planarians. Together, these results identify a novel role of Tnfaip2 and exoc3 in controlling lipid metabolism, which is essential for ESC differentiation and planarian organ maintenance. Synopsis: This study shows that lipid metabolism is required for mouse ESC differentiation and organ maintenance in planarians. Tnfaip2/Exoc3 ‐mediated induction of lipid metabolism is essential for embryonic stem (ES) cell differentiation and organ maintenance in planarians. Supplementation of fatty acid restores the differentiation potential of Tnfaip2 ‐deficient ES cells as well as organ homeostasis in planarians lacking Smed‐exoc3. Screening for genes with a role in pluripotency induction can be combined with in vivo planarian studies to identify factors that control stem cell differentiation and organ maintenance. Abstract : This study shows that lipid metabolism is required for mouse ESC differentiation and organ maintenance in planarians.